PRESTASI PENGEMUDI TRUK ANGKUTAN DI SUATU PENGUSAHAAN HUTAN DI KALIMANTAN BARAT - Dulsalam Dulsalam; Sukanda Sukanda (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
An investigation on logging truck drivers performances was carried out at a logging company in West Kalimantan in 1988. Seven logging truck drivers were observed using seven Nissan TZ 50 semi-trailer logging trucks (made in 1979). The purpose of this investigation is to find out logging truck drivers performances necessary for logging companies to plan their employment in hauling activity. For this purpose, the investigation was done through work time study. The investigation comes to the following conclusions : PT Duadja II employs several logging truck drivers having various skills. Nissan TZ 50 semi-trailer logging trucks are used to transport logs from the forest to log pond.Average performances of A, B, C, D, E, F, and G logging truck drivers were 765.79, 695.85, 652.56, 843.31, 745.07, 709.20, and 759.18 m3km/hour, respectively.The performances among logging truck drivers were significantly different due to the differences in load volumes and logging truck speeds as well as drivers' age and education levels.